Lupus Pernio-A Rare Case Report (Medicine Today, 2013)
Lupus Pernio is a chronic form of Sarcoidosis and it is a poor prognostic factor. It is commonly associated with bone cyst and pulmonary fibrosis. Spontaneous remission is rare. On this occasion we are reporting a case of 25 year old lady presented with a well defined erythematous plaque on the tip of the nose for last 8 years without any associated findings.DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15016 Medicine Today 2012 Vol.24(2): 87-88